Use of powered air-purifying respirators during surgical interventions. Issue 3 (25th January 2021) - Hardy, N; Dalli, J; Khan, M F; McCaul, C; O'Keeffe, D; Traynor, O; Jerry, J; Brady, D; Cahill, R A
Abstract : This clinical study confirms user acceptability of PAPR during surgery both at operating room team level as well as by groups of surgeons, anaesthesiologists and nursing level. While some care is needed in the use of this equipment, surgery can be performed safely with satisfactory user experience. Therefore PAPR is useable for surgery but scope exists for improvement.